Effects of omega-3 polyunsaturated fatty acid supplementation on cognitive functioning in youth at ultra-high risk for psychosis: secondary analysis of the NEURAPRO randomised controlled trial. Issue 5 (8th September 2022) - Cheng, Nicholas; McLaverty, Alison; Nelson, Barnaby; Markulev, Connie; Schäfer, Miriam R.; Berger, Maximus; Mossaheb, Nilufar; Schlögelhofer, Monika; Smesny, Stefan; Hickie, Ian B.; Berger, Gregor E.; Chen, Eric Y. H.; et al.
Abstract : Background: Cognitive impairments are well-established features of psychotic disorders and are present when individuals are at ultra-high risk for psychosis. However, few interventions target cognitive functioning in this population. Aims: To investigate whether omega-3 polyunsaturated fatty acid ( n −3 PUFA) supplementation improves cognitive functioning among individuals at ultra-high risk for psychosis. Method: Data ( N = 225) from an international, multi-site, randomised controlled trial (NEURAPRO) were analysed. Participants were given omega-3 supplementation (eicosapentaenoic acid and docosahexaenoic acid) or placebo over 6 months. Cognitive functioning was assessed with the Brief Assessment of Cognition in Schizophrenia (BACS). Mixed two-way analyses of variance were computed to compare the change in cognitive performance between omega-3 supplementation and placebo over 6 months. An additional biomarker analysis explored whether change in erythrocyte n −3 PUFA levels predicted change in cognitive performance. Results: The placebo group showed a modest greater improvement over time than the omega-3 supplementation group for motor speed ( ηp 2 = 0.09) and BACS composite score ( ηp 2 = 0.21). After repeating the analyses without individuals who transitioned, motor speed was no longer significant ( ηp 2 = 0.02), but the composite score remained significant ( ηp 2 = 0.02). Change in erythrocyte n-3 PUFA levels did not predict change in cognitive performance over 6 months. Conclusions: We found no evidence to support the use of omega-3 supplementation to improve cognitive functioning in ultra-high risk individuals. The biomarker analysis suggests that this finding is unlikely to be attributed to poor adherence or consumption of non-trial n −3 PUFAs.